Isolated Ectopia Lentis in Suspect of Weill-Marchesani Syndrome (WMS) - Priya Taufiq Arrachman; Ega Sekartika; Mutia Khanza; Dewi Rosarina; Dini Dharmawidiarini; Muhammad Hanun Mahyuddin (Vision Science and Eye Health Journal, 2022)
Introduction: The prevalence of Weill-Marchesani syndrome (WMS) is estimated to be 1:100.000 proportion of the population. Knowledge of the clinical and therapy of WMS is expected to improve the ability to diagnose this disease. In this case report, we will present a case of WMS in a tertiary hospital because our findings are rare and essential concerning the symptomatic treatment and visual rehabilitation. Case Presentation: A 7-year-old child presented with blurred vision in the left eye. The patient showed an abnormal facial appearance with short stature and brachydactyly on both hands. The patient had a history of Intracapsular cataract extraction (ICCE) surgery on the right eye with an indication of anterior lens subluxation. The patient then suffered aphakic glaucoma in the right eye after surgery. Anterior segment examination of the right eye found an aphakic lens, conjunctival sclerectasia, atrophic iris, and mid-dilation pupil. Anterior segment of the left eye found an atrophic iris and lens subluxation. From the clinical appearance and the ocular disturbance, such as brachydactyly and short stature, the patient was diagnosed with suspected WMS. The patient was treated with ICCE surgery on the left eye and micropulse transscleral cyclophotocoagulation (MP-TSCPC) surgery on the right eye. Conclusion: WMS is a rare disease. It is essential to make an early diagnosis of glaucoma and ectopia lentis in WMS patients because it will affect their vision.